Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

Conformational dynamics of intracellular tau protein revealed by cd and saxs - Gorantla, vijay nalini; Alexander, V. Shkumatov; Chinnathambi, Subashchandrabose (Methods in Molecular Biology, 2017)
A native conformation of a protein is essential for its biological role. In certain conditions, some proteins show non-native conformations, leading to aggregation, which in turn may produce severe pathologies. Such physiological conditions are classified as protein misfolding diseases. Alzheimer’s disease (AD) is the most common form of dementia. Extracellular senile plaques formed by Amyloid β and intracellular aggregates formed by microtubule-associated protein Tau (MAPT) are the hallmarks of AD. Physiological role of MAPT is to maintain the integrity and stability of microtubules, however it tends to self-aggregate forming intracellular paired helical filaments (PHFs) during AD. MAPT is also subjected to various post-translational modifications such as phosphorylation, glycosylation, truncation, and acetylation. Being natively unfolded, MAPT is prone to full characterization at atomic level. Small-angle X-ray scattering (SAXS) is often applied in combination with other biophysical methods, like nuclear magnetic resonance (NMR), circular dichroism (CD), fluorescence spectroscopy, analytical ultracentrifugation (AUC), or dynamic light scattering (DLS) to characterize natively unfolded systems. Here we describe the practical aspects of MAPT characterization by SAXS and CD in detail as well as outline the inferred structural and functional implications.

Multi-faceted role of melatonin in neuroprotection and amelioration of tau aggregates in alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2018)
Alzheimer's disease (AD) is one of the major age related neurodegenerative diseases whose pathology arises due to the presence of two distinct protein aggregates, viz., amyloid-beta plaques in extracellular matrix and tau neurofibrillary tangles in neurons. Multiple factors play a role in AD pathology, which includes familial mutations, oxidative stress, and post-translational modifications. Melatonin is an endocrine hormone, secreted during darkness, derived from tryptophan, and produced mainly by the pineal gland. It is an amphipathic molecule, which makes it suitable to cross not only blood-brain barrier, but also to enter several other subcellular compartments like mitochondria and endoplasmic reticulum. In this context, the neuroprotective effect of melatonin may be attributed to its role as an antioxidant. Melatonin's pleiotropic function as an antioxidant and neuroprotective agent has been widely studied. However, its direct effect on the aggregation of tau and amyloid-beta needs to be explored. Furthermore, an important aspect of its function is its ability to regulate the process of phosphorylation of tau by affecting the function of kinases and phosphatases. In this review, we are focusing on the pleiotropic function of melatonin on the aspect of its neuroprotective function in tau pathology, which includes antioxidant function, regulation of enzymes, including kinases and enzymes involved in free radical scavenging and mitochondrial protection.
Keywords: Alzheimer's disease; hyperphosphorylation; melatonin; mitochondria; Protein aggregation; tau protein

Prion-like propagation of post-translationally modified tau in alzheimer's disease: a hypothesis - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
The microtubule-associated protein Tau plays a key role in the neuropathology of Alzheimer's disease by forming intracellular neurofibrillary tangles. Tau in the normal physiological condition helps stabilize microtubules and transport. Tau aggregates due to various gene mutations, intracellular insults and abnormal post-translational modifications, phosphorylation being the most important one. Other modifications which alter the function of Tau protein are glycation, nitration, acetylation, methylation, oxidation, etc. In addition to forming intracellular aggregates, Tau pathology might spread in a prion-like manner as revealed by several in vitro and in vivo studies. The possible mechanism of Tau spread can be via bulk endocytosis of misfolded Tau species. The recent studies elucidating this mechanism have mainly focussed on the aggregation and spread of repeat domain of Tau in the cell culture models. Further studies are needed to elucidate the prion-like propagation property of full-length Tau and its aggregates in a more intense manner in vitro as well as in vivo conditions. Varied post-translational modifications can have discrete effects on aggregation propensity of Tau as well as its propagation. Here, we review the prion-like properties of Tau and hypothesize the role of glycation in prion-like properties of Tau. This post-translationally modified Tau might have an enhanced propagation property due to differential properties conferred by the modifications.
Keywords: Alzheimer disease; Post-translational modifications of tau; Propagation of tau; Tau; Tauopathies

Tau protein squired by molecular chaperones during alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive neuronal loss, caused by misfolding and accumulation of tau and Amyloid -42. Cellular mechanisms involving phosphatases, chaperones, ubiquitin proteasome system (UPS) and aggresomes solubilize or remove these toxic aggregates. Chaperones such as Hsp70 and Hsp90 functions in folding tau to its native form or in the downstream degrade and eliminated tau from the cell. Chaperones are involved in lysosomal degradation of tau by a process called chaperone mediated autophagy (CMA). In pathological conditions, chaperones fail to remove the toxic tau species, leading to their accumulation. In this scenario, inhibiting the chaperone activity would aid in overcoming AD. Small molecules inhibitors against chaperone activity are known to be effective in the clearance of aberrant tau from cell. In this review, the aspects of inhibition and prevention of tau aggregates formation are discussed in terms of chaperone activity and their small molecule modulators.

Baicalein suppresses repeat tau fibrillization by sequestering oligomers - Sonawane, Shweta Kishor; Balmik, Abhishek Ankur; Boral, Debjyoti; Ramasamy, Sureshkumar; Chinnathambi, Subashchandrabose (Archives of Biochemistry and Biophysics, 2019)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by protein misfolding, aggregation and accumulation in the brain. A large number of molecules are being screened against these pathogenic proteins but the focus for therapeutics is shifting towards the natural compounds as aggregation inhibitors, mainly due to their minimum adverse effects. Baicalein is a natural compound belonging to the class of flavonoids isolated from the Chinese herb Scutellaria baicalensis. Here we applied fluorescence, absorbance, microscopy, MALDI-TOF spectrophotometry and other biochemical techniques to investigate the interaction between Tau and Baicalein in vitro. We found the aggregation inhibitory properties of Baicalein for the repeat Tau. Overall, the potential of Baicalein in dissolving the preformed Tau oligomers as well as mature fibrils can be of utmost importance in therapeutics for Alzheimer's disease.
Keywords: Alzheimer disease; Baicalein; Microtubule assembly; Paired helical filaments; Protein aggregation; tau protein

Microglial priming of antigen presentation and adaptive stimulation in Alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Cellular and Molecular Life Sciences, 2019)
The prominent pathological consequences of Alzheimer's disease (AD) are the misfolding and mis-sorting of two cellular proteins, amyloid-beta and microtubule-associated protein Tau. The accumulation of toxic phosphorylated Tau inside the neurons induces the increased processing of amyloid-beta-associated signaling cascade and vice versa. Neuroinflammation-driven synaptic depletion and cognitive decline are substantiated by the cross talk of activated microglia and astroglia, leading to neuron degeneration. Microglia are the brain-resident immune effectors that prove their diverse functions in maintaining CNS homeostasis via collaboration with astrocytes and T lymphocytes. Age-related senescence and chronic inflammation activate microglia with increased pro-inflammatory markers, oxidative damage and phagocytosis. But the improper processing of misfolded protein via lysosomal pathway destines the spreading of 'seed' constituents to the nearby healthy neurons. Primed microglia process and present self-antigen such as amyloid-beta and modified Tau to the infiltrated T lymphocytes through MHC I/II molecules. After an effective conversation with CD4(+) T cells, microglial phenotype can be altered from pro-active M1 to neuro-protective M2 type, which corresponds to the tissue remodeling and homeostasis. In this review, we are focusing on the change in functionality of microglia from innate to adaptive immune response in the context of neuroprotection, which may help in the search of novel immune therapy in AD.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Photoexcited toluidine blue inhibits tau aggregation in Alzheimer's disease - Dubey, Tushar; Nalini, Gorantla Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The aggregates of microtubule-associated protein Tau are considered as a major hallmark of Alzheimer's disease. Tau aggregates accumulate intracellularly leading to neuronal toxicity. Numerous approaches have been targeted against Tau protein aggregation, which include application of synthetic and natural compounds. Toluidine blue is a basic dye of phenothiazine family, which on irradiation with a 630 nm light gets converted into a photoexcited form, leading to generation of singlet oxygen species. Methylene blue is the parent compound of toluidine blue, which has been reported to be potent against tauopathy. In the present work, we studied the potency of toluidine blue and photoexcited toluidine blue against Tau aggregation. Biochemical and biophysical analyses using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, ThS fluorescence, circular dichroism spectroscopy, and electron microscopy suggested that toluidine blue inhibited the aggregation of Tau in vitro. The photoexcited toluidine blue potentially dissolved the matured Tau fibrils, which indicated the disaggregation property of toluidine blue. The cell biology studies including the cytotoxicity assay and reactive oxygen species (ROS) production assay suggested toluidine blue to be a biocompatible dye as it reduced ROS levels and cell death. The photoexcited toluidine blue modulates the cytoskeleton network in cells, which was supported by immunofluorescence studies of neuronal cells. The studies in a UAS Tau E14 transgenic Drosophila model suggested that photoexcited toluidine blue was potent to restore the survival and memory deficits of Drosophila. The overall finding of our studies suggested toluidine blue to be a potent molecule in rescuing the Tau-mediated pathology by inhibiting its aggregation, reducing the cell death, and modulating the tubulin levels and behavioral characteristics of Drosophila. Thus, toluidine blue can be addressed as a potent molecule against Alzheimer's disease.

Protein-capped metal nanoparticles inhibit tau aggregation in alzheimer's disease - Sonawane, Shweta Kishor; Ahmad, Absar; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The Alzheimer's disease (AD) therapeutic research is yielding a large number of potent molecules. The nanoparticle-based therapeutics against the protein aggregation in AD is also taking a lead especially with amyloid-beta as a primary target. In this work, we have screened for the first time protein-capped (PC) metal nanoparticles for their potency in inhibiting Tau aggregation in vitro. We present a novel function of PC-Fe3O4 and PC-CdS nanoparticles as potent Tau aggregation inhibitors by fluorescence spectrometry, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and electron microscopy. We demonstrate that the biologically synthesized PC-metal nanoparticles, especially iron oxide do not affect the viability of neuroblastoma cells. Moreover, PC-CdS nanoparticles show dual properties of inhibition and disaggregation of Tau. Thus, the nanoparticles can take a lead as potent Tau aggregation inhibitors and can be modified for specific drug delivery due to their very small size. The current work presents unprecedented strategy to design anti-Tau aggregation drugs, which provides interesting insights to understand the role of biological nanostructures in Alzheimer's disease.

Actin-mediated microglial chemotaxis via G-protein coupled purinergic receptor in alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease mainly associated with aging, oxidative stress and genetic mutations. There are two pathological proteins involved in AD; Amyloid-beta peptide and microtubule-associated protein Tau (MAPT). The beta- and gamma-secretase enzyme cleaves the Amyloid precursor protein, which results in the formation of extracellular plaques in brain. While, Tau undergoes hyperphosphorylation and other post-translational modifications (PTMs), which eventually generates Tau oligomers, and intracellular neurofibrillary tangles (NFTs) in neurons. Moreover, the brain-resident glia and infiltrated macrophages elevate the level of CNS inflammation, which trigger the oxidative damage of neuronal circuits by reactive oxygen species (ROS) and Nitric oxide (NO). Microglia is the primary immune cell in the CNS, which is continuously surveilling the neuronal synapses and pathogen invasion. Microglia in the resting state is called `Ramified', which possess long surveilling extensions with a small cell body. But, upon activation, microglia retracts the cellular extensions and transform into round migratory cells, called as `Amoeboid' state. Activated microglia undergoes actin remodeling by forming lamellipodia and filopodia, which directs the migratory axis while podosomes formed are involved in extracellular matrix degradation for invasion. Protein-aggregates in malfunctioning synapses and in CNS milieu can be detected by microglia, which results in its activation and migration. Subsequently, the phagocytosis of synapses leads to the inflammatory burst and memory loss. The extracellular nucleotides released from damaged neurons and the cytokine-chemokine gradients allow the neighboring microglia and macrophages to migrate-infiltrate at the site of neuronal-damage. The ionotropic (P2XR) and metabotropic (P2YR) purinergic receptor recognize extracellular ATP/ADP, which propagates through the intracellular calcium signaling, chemotaxis, phagocytosis and inflammation. The P2Y receptors give `find me' or `eat me' signals to microglia to either migrate or phagocytose cellular debris. Further, the actin cytoskeleton helps microglia to mediate directed chemotaxis and neuronal repair during neurodegeneration. Hence, we aim to emphasize the connection between purinergic signaling and actin-driven mechanical movements of microglia for migration and inflammation in AD. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: actin remodeling; Alzheimer's disease; microglia; P2Y signaling; purinergic GPCRs; Tauopathy

Autophagic pathways to clear the tau aggregates in alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin-proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.
Keywords: Alzheimer's disease; Chaperone-mediated autophagy; Lysosome-associated membrane proteins-2A; Macroautophagy; Neurofibrillary tangles; Tau; Tau degradation; Ubiquitin-proteasome system

Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.

Cobalt-based metal complexes prevent repeat tau aggregation and nontoxic to neuronal cells - Gorantla, V. Nalini; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease (AD) is a fatal neurodegenerative disorder with an alarming increase in the death rate every year. AD is characterised by an aberrant accumulation of proteins in the form of aggregates. The axonal microtubule-associated protein Tau and arnyloid-beta undergo structural transition to beta-sheet rich structure and form aggregates in neuronal soma as well as in the extracellular region. The loss of Tau from microtubules leads to the disintegration of axon and causing neuronal degeneration. This led to the development of effective drugs against AD, to prevent Tau aggregation. Here, we synthesized and screen metal-based complexes to prevent Tau protein aggregation. ThS fluorescence and TEM suggested the role of synthetic cobalt complexes in inhibiting Tau aggregation. CD spectroscopy showed that these complexes prevented conformational changes in Tau to beta-sheet. CBMCs were not toxic at lower concentrations and formed non-toxic Tau species. L1 and L2 prevented membrane leakage: whereas, higher concentrations of L3 caused membrane leakage as observed by LDH release assay. The overall results indicate the synthetic cobalt complexes to be a promising molecule against AD. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cobalt-based metals; Tau Aggregation; Tau inhibition; Tau toxicity

Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

G-protein coupled receptors and tau-different roles in alzheimer's disease - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Post-translational modification of Tau, a microtubule-associated protein in the neuronal cell, plays a major role in Alzheimer's disease. Tau is an axonal protein expressed in mature neurons that promote the self-assembly of tubulin into microtubules and its stabilization in neurons. Phosphorylation of Tau makes it prone to aggregation at the intra-neuronal region leading to impaired neurotransmission and dementia. Tau aggregates undergo trans-cellular propagation by the release of fibrillar species into the extra-cellular environment from damaged and infected neurons that can be internalized by neighbouring neuronal and glia cells and promotes aggregation in healthy cells. G-protein coupled receptors, the largest group of seven transmembrane receptors, are involved in neuronal signal transduction in response to various signals such as hormones and neurotransmitters. In Alzheimer's disease, GPCRs are involved in phosphorylation of Tau through various downstream kinases such as GSK-3b, CDK-5 and ERKs signalling cascade. Several neuronal GPCRs that are involved in Tau phosphorylation are elaborated in this review. The astrocytic GPCR, Tau phosphorylation mediated by CaS receptors and its propagation by exosomes are also elaborated. In the microglia, the extra-cellular Tau binding to a chemokine GPCR, CX3CR1 triggers its internalization, whereas Tau phosphorylation at specific sites decreases its binding affinity to this receptor. Here we highlight the role of GPCRs in Tau phosphorylation and Tau interaction in different cells of the nervous system. Hence, the role of GPCRs are attaining more attention in the therapeutic field of Alzheimer's disease. Specific agonists/antagonists and allosteric modulators could be the potential target for therapy against GPCR-mediated Tau phosphorylation in Alzheimer's disease. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Alzheimer's disease; GPCRs; microglia; Tau internalization; Tau phosphorylation; Tau propagation

HDAC6 ZnF UBP as the modifier of tau structure and function - Balmik, Abhishek Ankur; Chidambaram, Hariharakrishnan; Dangi, Abha; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochemistry, 2020)
Histone deacetylase 6 is a class H histone deacetylase primarily present in the cytoplasm and involved in the regulation of various cellular functions. It consists of two catalytic deacetylase domains and a unique zinc finger ubiquitin binding protein domain, which sets it apart from other HDACs. HDAC6 is known to regulate cellular activities by modifying the function of microtubules, HSP90, and cortactin through deacetylation. Apart from the catalytic activity of HDAC6, it interacts with other proteins through either the SE14 domain or the ZnF UBP domain to modulate their functions. Here, we have studied the role of the HDAC6 ZnF UBP domain as a modifier of Tau aggregation by its direct interaction with the polyproline region/repeat region of Tau. Interaction of HDAC6 ZnF UBP with Tau was found to reduce the propensity of Tau to self-aggregate and to disaggregate preformed aggregates in a concentration-dependent manner and also bring about the conformational changes in Tau protein. The interaction of HDAC6 ZnF UBP with Tau results in its degradation, suggesting either proteolytic activity of HDAC6 ZnF UBP or its role in enhancing autoproteolysis of Tau.

Interaction of Tau with the chemokine receptor, CX3CR1 and its effect on microglial activation, migration and proliferation - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (Cell and Bioscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease that leads to progressive loss of memory and dementia. The pathological hallmarks of AD include extracellular accumulation of amyloid-beta peptides forming senile plaques and intracellular accumulation of Tau oligomers and filamentous species. Tau is a microtubule-binding protein that stabilizes tubulin to form microtubules under physiological condition. In AD/ pathological condition, Tau detaches from microtubules and aggregates to form oligomers of different sizes and filamentous species such as paired helical filaments. Microglia are the resident brain macrophages that are involved in the phagocytosis of microbes, cellular debris, misfolded and aggregated proteins. Chemokine receptor, CX3CR1 is mostly expressed on microglia and is involved in maintaining the microglia in a quiescent state by binding to its ligand, fractalkine (CX3CL1), which is expressed in neurons as both soluble or membrane-bound state. Hence, under physiological conditions, the CX3CR1/CX3CL1 axis plays a significant role in maintaining the central nervous system (CNS) homeostasis. Further, CX3CR1/CX3CL1 signalling is involved in the synthesis of anti-inflammatory cytokines and also has a significant role in cytoskeletal rearrangement, migration, apoptosis and proliferation. In AD brain, the expression level of fractalkine is reduced, and hence Tau competes to interact with its receptor, CX3CR1. In microglia, phagocytosis and internalization of extracellular Tau species occurs in the presence of a chemokine receptor, CX3CR1 which binds directly to Tau and promotes its internalization. In this review, the pathophysiological roles of CX3CR1/fractalkine signalling in microglia and neurons at different stages of Alzheimer's disease and the possible role of CX3CR1/Tau signalling has been widely discussed.
Keywords: Alzheimer's disease; CX3CR1 receptor; Fractalkine; microglia; Neuron; Tau

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Melatonin reduces GSK3 beta-mediated tau phosphorylation, enhances Nrf2 nuclear translocation and anti-inflammation - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (ASN Neuro, 2020)
Alzheimer's disease is a neuropathological condition with abnormal accumulation of extracellular Amyloid-beta plaques and intracellular neurofibrillary tangles of Microtubule-associated protein Tau (Tau) in the brain. In pathological conditions, Tau undergoes post-translational modifications such as hyperphosphorylation by the activity of cellular kinases, which eventually leads to protein aggregation in neurons. Melatonin is a neuro-hormone that is mainly secreted from the pineal gland and functions to modulate the cellular kinases. In our study, we have checked the neuroprotective function of Melatonin by MTT and LDH assay, where Melatonin inhibited the Tau aggregates-mediated cytotoxicity and membrane leakage in Neuro2A cells. The potency of Melatonin has also been studied for the quenching of intracellular reactive oxygen species level by DCFDA assay and caspase 3 activity. Melatonin was shown to reduce the GSK3 beta mRNA and subsequent protein level as well as the phospho-Tau level (pThr181 and pThr212-pSer214) in okadaic acid-induced Neuro2A cells, as observed by western blot and immunofluorescence assay. Further, Melatonin has increased the cellular Nrf2 level and its nuclear translocation as an oxidative stress response in Tauopathy. The Melatonin was found to induce pro- and anti-inflammatory cytokines levels in N9 microglia. The mRNA level of cellular kinases such as as-GSK3 beta, MAPK were also studied by qRT-PCR assay in Tau-exposed N9 and Neuro2A cells. The immunomodulatory effect of Melatonin was evident as it induced IL-10 and TGF-beta cytokine levels and activated MAP3K level in Tau-exposed microglia and neurons, respectively. Melatonin also downregulated the mRNA level of pro-inflammatory markers, IL-1 beta and Cyclooxygenase-2 in N9 microglia. Together, these findings suggest that Melatonin remediated the cytokine profile of Tau-exposed microglia, reduced Tau hyperphosphorylation by downregulating GSK3 beta level, and alleviated oxidative stress via Nrf2 nuclear translocation.
Keywords: Alzheimer’ Anti-inflammatory; GSK3β melatonin; microglia; neurodegeneration; Nrf2; s disease; Tau hyperphosphorylation

P301 L, an FTDP-17 mutant, exhibits enhanced glycation in vitro - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2020)
Background: Frontotemporal dementia and parkinsonism-linked to chromosome-17 are a group of diseases with tau mutations leading to primary tauopathies which include progressive supranuclear palsy, corticobas al syndrome, and frontotemporal lobar degeneration. Alzheimer's disease is a non-primary tauopathy, which displays tau neuropathology of excess tangle formation and accumulation. FTDP-17 mutations are responsible for early onset of AD, which can be attributed to compromised physiological functions due to the mutations. Tau is a microtubule-binding protein that secures the integrity of polymerized microtubules in neuronal cells. It malfunctions owing to various insults and stress conditions-like mutations and post-translational modifications. Objective: In this study, we modified the wild type and tau mutants by methyl glyoxal and thus studied whether glycation can enhance the aggregation of predisposed mutant tau. Methods: Tau glycation was studied by fluorescence assays, SDS-PAGE analysis, conformational evaluation, and transmission electron microscopy. Results: Our study suggests that FTDP-17 mutant P301 L leads to enhanced glycation-induced aggregation as well as advanced glycation end products formation. Glycation forms amorphous aggregates of tau and its mutants without altering its native conformation. Conclusion: The metabolic anomalies and genetic predisposition have found to accelerate tau-mediated neurodegeneration and prove detrimental for the early-onset of Alzheimer's disease.
Keywords: advanced glycation end products; Alzheimer's disease; FTDP-17; tau glycation

Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2020)
Background Alzheimer's disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-beta plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40(WT) oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-beta sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40(WT) oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11(+) Iba1(high) microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer's disease condition.
Keywords: Actin; activation; Alzheimer's disease; microglia; migration; neurodegeneration; Tau Oligomers; Tauopathy

Photodynamic exposure of Rose-Bengal inhibits Tau aggregation and modulates cytoskeletal network in neuronal cells - Dubey, Tushar; Gorantla, Nalini Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The intracellular Tau aggregates are known to be associated with Alzheimer's disease. The inhibition of Tau aggregation is an important strategy for screening of therapeutic molecules in Alzheimer's disease. Several classes of dyes possess a unique property of photo-excitation, which is applied as a therapeutic measure against numerous neurological dysfunctions. Rose Bengal is a Xanthene dye, which has been widely used as a photosensitizer in photodynamic therapy. The aim of this work was to study the protective role of Rose Bengal against Tau aggregation and cytoskeleton modulations. The aggregation inhibition and disaggregation potency of Rose Bengal and photo-excited Rose Bengal were observed by in-vitro fluorescence, circular dichroism, and electron microscopy. Rose Bengal and photo-excited Rose Bengal induce minimal cytotoxicity in neuronal cells. In our studies, we observed that Rose Bengal and photo-excited Rose Bengal modulate the cytoskeleton network of actin and tubulin. The immunofluorescence studies showed the increased filopodia structures after photo-excited Rose Bengal treatment. Furthermore, Rose Bengal treatment increases the connections between the cells. Rose Bengal and photo-excited Rose Bengal treatment-induced actin-rich podosome-like structures associated with cell membranes. The in-vivo studies on UAS E-14 Tau mutant Drosophila suggested that exposure to Rose Bengal and photo-excited Rose Bengal efficiency rescues the behavioural and memory deficit in flies. Thus, the overall results suggest that Rose Bengal could have a therapeutic potency against Tau aggregation.

Protein misfolding and aggregation of tau protein in alzheimer’s disease - Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Advances in Bioengineering, 2020)
Protein misfolding has interestingly been referred to as the ‘dark side’ of the protein world. The cytotoxicity of misfolded and unfolded polypeptides is due to an overwhelmed quality control system, mainly comprising molecular chaperones to assist in folding, the unfolded protein response (UPR) in the endoplasmic reticulum and the heat shock response (HSR) in the cytosol, which are aimed at clearing misfolded proteins and their early aggregates. When misfolded/unfolded polypeptides exceed the quality control measures of the chaperone–ubiquitin–proteasome clearing system, they form toxic pre-fibrillar aggregates which interact with the cell membrane, disrupting redox potential due to aggregate organization into non-specific membrane pores. In most cases, increases in intracellular free Ca²⁺ and consequent disruption of the redox potential are among the earliest biochemical alterations in exposed cells. An improved understanding of the mechanisms of protein misfolding and intermediate structures that lead from monomers to oligomers ready to aggregate could provide crucial impetus to therapeutic interventions such as upregulating molecular chaperone machinery, use of antibodies and high throughput screening of promising candidate molecules.

Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

Role of dietary fatty acids in microglial polarization in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (2020)
Microglial polarization is an utmost important phenomenon in Alzheimer's disease that influences the brain environment. Polarization depends upon the types of responses that cells undergo, and it is characterized by receptors present on the cell surface and the secreted cytokines to the most. The expression of receptors on the surface is majorly influenced by internal and external factors such as dietary lipids. Types of fatty acids consumed through diet influence the brain environment and glial cell phenotype and types of receptors on microglia. Reports suggest that dietary habits influence microglial polarization and the switching of microglial phenotype is very important in neurodegenerative diseases. Omega-3 fatty acids have more influence on the brain, and they are found to regulate the inflammatory stage of microglia by fine-tuning the number of receptors expressed on microglia cells. In Alzheimer's disease, one of the pathological proteins involved is Tau protein, and microtubule-associated protein upon abnormal phosphorylation detaches from the microtubule and forms insoluble aggregates. Aggregated proteins have a tendency to propagate within the neurons and also become one of the causes of neuroinflammation. We hypothesize that tuning microglia towards anti-inflammatory phenotype would reduce the propagation of Tau in Alzheimer's disease.
Keywords: Fatty acids; Microglial polarization; Omega-3 fatty acids; Tau inflammation; Tau phagocytosis; Tau spreading; Tauopathy

Role of microglia in regulating cholesterol and tau pathology in alzheimer's disease - Nanjundaiah, Shwetha; Chidambaram, Hariharakrishnan; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Cholesterol, a principal constituent of the cell membrane, plays a crucial role in the brain by regulating the synaptic transmission, neuronal signaling, as well as neurodegenerative diseases. Defects in the cholesterol trafficking are associated with enhanced generation of hyperphosphorylated Tau and Amyloid-beta protein. Tau, a major microtubule-associated protein in the brain, is the key regulator of the mature neuron. Abnormally hyperphosphorylated Tau hampers the major functions related to microtubule assembly by promoting neurofibrillary tangles of paired helical filaments, twisted ribbons, and straight filaments. The observed pathological changes due to impaired cholesterol and Tau protein accumulation cause Alzheimer's disease. Thus, in order to regulate the pathogenesis of Alzheimer's disease, regulation of cholesterol metabolism, as well as Tau phosphorylation, is essential. The current review provides an overview of (1) cholesterol synthesis in the brain, neurons, astrocytes, and microglia; (2) the mechanism involved in modulating cholesterol concentration between the astrocytes and brain; (3) major mechanisms involved in the hyperphosphorylation of Tau and amyloid-beta protein; and (4) microglial involvement in its regulation. Thus, the answering key questions will provide an in-depth information on microglia involvement in managing the pathogenesis of cholesterol-modulated hyperphosphorylated Tau protein.
Keywords: Alzheimer's disease; Amyloid-beta protein; Cholesterol; microglia; Tau hyperphosphorylation

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Alpha-Linolenic acid inhibits Tau aggregation and modulates Tau conformation - Desale, Smita Eknath; Dubey, Tushar; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2021)
Alzheimer's disease is characterized by important patho-proteins, which being composed of Amyloid-beta, plaques and intracellular neurofibrillary tangles of Tau. Intrinsically disordered protein tau has several interacting partners, which are necessary for its normal functioning. Tau has been shown to interact with various proteins, nucleic acid, and lipids. alpha-Linolenic acid (ALA) a plant-based omega-3 fatty acid has been studied for its role as neuroprotective and beneficial fatty add in the brain. In this study, we are focusing on the ability of ALA to induce spontaneous assembly in tau protein. ALA inhibited the Tau aggregation as indicated by reduced ThS fluorescence kinetics, which indicates no aggregation of Tau. Similarly, SDS-PAGE analysis supported that ALA exposure inhibited the aggregation as no higher-order tau species were observed. Along with its ability to impede the aggregation of Tau, ALA also maintains a native random coiled structure, which was estimated by CD spectroscopy. Finally, TEM analysis showed that the formation of Tau fibrils was found to be discouraged by ALA. Hence, conclusion of the study suggested that ALA profoundly inhibited aggregation of Tau and maintained it's the random-coil structure. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-linolenic acid; Alzheimer's disease; Free fatty adds; Tau conformation; Tau fibrillization

Alpha-Linolenic acid modulates phagocytosis and endosomal pathways of extracellular Tau in microglia - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Adhesion & Migration, 2021)
Microglia, the resident immune cells, were found to be activated to inflammatory phenotype in Alzheimer's disease (AD). The extracellular burden of amyloid-beta plaques and Tau seed fabricate the activation of microglia. The seeding effect of extracellular Tau species is an emerging aspect to study about Tauopathies in AD. Tau seeds enhance the propagation of disease along with its contribution to microglia-mediated inflammation. The excessive neuroinflammation cumulatively hampers phagocytic function of microglia reducing the clearance of extracellular protein aggregates. Omega-3 fatty acids, especially docosahexaenoic acid and eicosapentaenoic acid, are recognized to induce anti-inflammatory phenotype of microglia. In addition to increased cytokine production, omega-3 fatty acids enhance phagocytic receptors expression in microglia. In this study, we have observed the phagocytosis of extracellular Tau in the presence of alpha-linolenic acid (ALA). The increased phagocytosis of extracellular Tau monomer and aggregates have been observed upon ALA exposure to microglia cells. After internalization, the degradation status of Tau has been studied with early and late endosomal markers Rab5 and Rab7. Further, the lysosome-mediated degradation of internalized Tau was studied with LAMP-2A, a lysosome marker. The enhanced migratory ability in the presence of ALA could be beneficial for microglia to access the target and clear it. The increased migration of microglia was found to induce the microtubule-organizing center repolarization. The data indicate that the dietary fatty acids ALA could significantly enhance phagocytosis and intracellular degradation of internalized Tau. Our results suggest that microglia could be influenced to reduce extracellular Tau seed with dietary fatty acids.
Keywords: alpha-linolenic acid; endosomal markers; Fatty acids; MTOC repolarization; Phagocytosis; Tauopathy

Amyloid-beta-derived peptidomimetics inhibits tau aggregation - Gorantla, V. Nalini; Sunny, Lisni P.; Rajasekhar, Kolla; Nagaraju, Pramod G.; Priyadarshini, Poornima C. G.; Govindaraju, Thimmaiah; Chinnathambi, Subashchandrabose (ACS Omega, 2021)
The aggregation of tau protein is one of the hallmarks for Alzheimer's disease, resulting in neurodegeneration. The peptidomimetics strategy to prevent tau aggregation is more specific over other small molecules. In the present study, we analyzed the effect of amyloid-beta-derived peptidomimetics for inhibiting heparin-induced tau aggregation in vitro. These peptides and their derivatives were known to prevent aggregation of amyloid-beta. KLVFF is a hydrophobic sequence of the pentapeptide that prevented tau aggregation as observed by thioflavin S fluorescence, transmission electron microscopy, and circular dichroism spectroscopy. P4 and P5 also prevented assembly of tau into aggregates and formed short fibrils. The beta-sheet breaker LPFFD was however ineffective in preventing tau aggregation. The peptides further demonstrated reversal of tau-induced cytotoxicity in a dose-dependent manner. Our results suggested that these peptides can also be used to inhibit tau aggregation and also, toxicity induced by tau could be considered as potential molecules that have an effect on tau as well as amyloid-beta.

Autophagic pathways to clear the tau aggregates in alzheimer’s disease - vijay nalini, Gorantla; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2021)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin–proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.

Baicalein inhibits heparin-induced Tau aggregation by initializing non-toxic Tau oligomer formation - Sonawane, Shweta Kishor; Uversky, Vladimir N.; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Amyloid aggregate deposition is the key feature of Alzheimer's disease. The proteinaceous aggregates found in the afflicted brain are the intra-neuronal neurofibrillary tangles formed by the microtubule-associated protein Tau and extracellular deposits, senile plaques, of amyloid beta (A beta) peptide proteolytically derived from the amyloid precursor protein. Accumulation of these aggregates has manifestations in the later stages of the disease, such as memory loss and cognitive inabilities originating from the neuronal dysfunction, neurodegeneration, and brain atrophy. Treatment of this disease at the late stages is difficult, and many clinical trials have failed. Hence, the goal is to find means capable of preventing the aggregation of these intrinsically disordered proteins by inhibiting the early stages of their pathological transformations. Polyphenols are known to be neuroprotective agents with the noticeable potential against many neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Prion diseases. Methods: We analyzed the capability of Baicalein to inhibit aggregation of human Tau protein by a multifactorial analysis that included several biophysical and biochemical techniques. Results: The potency of Baicalein, a polyphenol from the Scutellaria baicalensis Georgi, against in vitro Tau aggregation and PHF dissolution has been screened and validated. ThS fluorescence assay revealed the potent inhibitory activity of Baicalein, whereas ANS revealed its mechanism of Tau inhibition viz. by oligomer capture and dissociation. In addition, Baicalein dissolved the preformed mature fibrils of Tau thereby possessing a dual target action. Tau oligomers formed by Baicalein were non-toxic to neuronal cells, highlighting its role as a potent molecule to be screened against AD. Conclusion: In conclusion, Baicalein inhibits aggregation of hTau40 by enhancing the formation of SDS-stable oligomers and preventing fibril formation. Baicalein-induced oligomers do not affect the viability of the neuroblastoma cells. Therefore, Baicalein can be considered as a lead molecule against Tau pathology in AD.
Keywords: Alzheimer's disease; Baicalein; Tau dissolution; Tau inhibition; Tau Oligomers

Epigallocatechin-3-gallate modulates tau post-translational modifications and cytoskeletal network - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Oncotarget, 2021)
BACKGROUND: Alzheimer's disease is a type of dementia denoted by progressive neuronal death due to the accumulation of proteinaceous aggregates of Tau. Post-translational modifications like hyperphosphorylation, truncation, glycation, etc. play a pivotal role in Tau pathogenesis. Glycation of Tau aids in paired helical filament formation and abates its microtubule-binding function. The chemical modulators of Tau PTMs, such as kinase inhibitors and antibody-based therapeutics, have been developed, but natural compounds, as modulators of Tau PTMs are not much explored. MATERIALS AND METHODS: We applied biophysical and biochemical techniques like fluorescence kinetics, oligomerization analysis and transmission electron microscopy to investigate the impact of EGCG on Tau glycation in vitro. The effect of glycation on cytoskeleton instability and its EGCG-mediated rescue were studied by immunofluorescence microscopy in neuroblastoma cells. RESULTS: EGCG inhibited methyl glyoxal (MG)-induced Tau glycation in vitro. EGCG potently inhibited MG-induced advanced glycation endproducts formation in neuroblastoma cells as well modulated the localization of AT100 phosphorylated Tau in the cells. In addition to preventing the glycation, EGCG enhanced actin-rich neuritic extensions and rescued actin and tubulin cytoskeleton severely disrupted by MG. EGCG maintained the integrity of the Microtubule Organizing Center (MTOC) stabilized microtubules by Microtubule-associated protein RP/EB family member 1 (EB1). CONCLUSIONS: We report EGCG, a green tea polyphenol, as a modulator of in vitro methylglyoxal-induced Tau glycation and its impact on reducing advanced glycation end products in neuroblastoma cells. We unravel unprecedented function of EGCG in remodeling neuronal cytoskeletal integrity.
Keywords: Alzheimer’s disease; tau glycation; Tau glycation inhibition; tau protein; Tau PTMs

Extracellular HDAC6 ZnF UBP domain modulates the actin network and post-translational modifications of Tau - Balmik, Abhishek Ankur; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Microtubule-associated protein Tau undergoes aggregation in Alzheimer`s disease (AD) and a group of other related diseases collectively known as Tauopathies. In AD, Tau forms aggregates, which are deposited intracellularly as neurofibrillary tangles. Histone deacetylase-6 (HDAC6) plays an important role in aggresome formation, where it recruits polyubiquitinated aggregates to the motor protein dynein. Methods: Here, we have studied the effects of HDAC6 ZnF UBP on Tau phosphorylation, ApoE localization, GSK-3 beta regulation and cytoskeletal organization in neuronal cells by immunocytochemical analysis. This analysis reveals that the cell exposure to the UBP-type zinc finger domain of HDAC6 (HDAC6 ZnF UBP) can modulate Tau phosphorylation and actin cytoskeleton organization. Results: HDAC6 ZnF UBP treatment to cells did not affect their viability and resulted in enhanced neurite extension and formation of structures similar to podosomes, lamellipodia and podonuts suggesting the role of this domain in actin re-organization. Also, HDAC6 ZnF UBP treatment caused increase in nuclear localization of ApoE and tubulin localization in microtubule organizing centre (MTOC). Therefore, our studies suggest the regulatory role of this domain in different aspects of neurodegenerative diseases. Upon HDAC6 ZnF UBP treatment, inactive phosphorylated form of GSK-3 beta increases without any change in total GSK-3 beta level. Conclusions: HDAC6 ZnF UBP was found to be involved in cytoskeletal re-organization by modulating actin dynamics and tubulin localization. Overall, our study suggests that ZnF domain of HDAC6 performs various regulatory functions apart from its classical function in aggresome formation in protein misfolding diseases.
Keywords: Actin; Cytoskeleton; HDAC6; Microtubule; neurodegeneration; Phosphorylation; Podonut; Podosomes; Tau; Tauopathies

Implications of valosin-containing protein in promoting autophagy to prevent tau aggregation - Chinnathambi, Subashchandrabose; Gorantla, Nalini Vijay (Neuroscience, 2021)
and cellular degradative mechanisms modulate Tau aggregation. During aging and neu-rodegenerative disorders, the cellular proteostasis is disturbed due to impaired protective mechanisms. This results in accumulation of aberrant Tau aggregates in the neuron that leads to microtubule destabilization and neuronal degeneration. The intricate mechanisms to prevent Tau aggregation involve chaperones, autophagy, and proteasomal system have gained main focus about concerning to therapeutic intervention. However, the thor-ough understanding of other key proteins, such as Valosin-containing protein (VCP), is limited. In various neu-rodegenerative diseases, the chaperone-like activity of VCP is involved in preventing protein aggregation and mediating the degradation of aberrant proteins by proteasome and autophagy. In the case of Tau aggregation associated with Alzheimer's disease, the importance of VCP is poorly understood. VCP is known to co-localize with Tau, and alterations in VCP cause aberrant accumulation of Tau. Nevertheless, the direct mechanism of VCP in altering Tau aggregation is not known. Hence, we speculate that VCP might be one of the key modulators in preventing Tau aggregation and can disintegrate Tau aggregates by directing its clearance by autophagy. = 2021 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Autophagy; segregase; Tau aggregates; Ubiquitin-proteasome system; valosin-containing protein

Influence of sodium caseinate, maltodextrin, pectin and their Maillard conjugate on the stability, in vitro release, anti-oxidant property and cell viability of eugenol-olive oil nanoemulsions - Nagaraju, Pramod G.; Sindhu, P.; Dubey, Tushar; Chinnathambi, Subashchandrabose; Priyadarshini, Poornima; Rao, Pooja J. (International Journal of Biological Macromolecules, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The influence of protein (sodium caseinate-SC), polysaccharide (maltodextrin-MD; pectin-PC) and their Maillard conjugates (sodium caseinate maltodextrin conjugate-SCMDC; sodium caseinate pectin conjugate-SCPCC) were studied on the physico-chemical and biological properties of eugenol nanoemulsions/powder. The chemical composition was optimized using Taguchi design. The particles size of eugenol nanoemulsions with SC, MD, PC, SCMDC and SCPCC were 104.6, 323.5, 1872, 181.7, and 454.4 nm, respectively while their zeta potentials were -31.2, -28.5, -21.4, -40.1 and -25.1 mV, respectively. Turbidity studies revealed higher stability of nanoemulsion prepared with Maillard conjugate (SCMDC) compared to protein or polysaccharides alone. The dispersion of SCMDC eugenol nanoparticles in buffer was prepared to study its stability at different pH (3.0, 5.0, and 7.0) and temperature (4°, 37°, 60 °C) range. In-vitro enzymatic release study showed 31 and 74% release of eugenol after 6 h at pH 2.4 and 7.4, respectively. In vitro antioxidant capacity of SCMDC encapsulated eugenol was higher than native eugenol, as demonstrated by free radical scavenging assays. In comparison to native eugenol, E:SCMDC eugenol showed reduced toxicity. These findings suggested that nanoencapsulated eugenol (E:SCMDC) have a huge potential in nutraceutical and therapeutic applications.

Methylation as a key regulator of Tau aggregation and neuronal health in Alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Neurodegenerative diseases like Alzheimer's, Parkinson's and Huntington's disease involves abnormal aggregation and accumulation of toxic proteins aggregates. Post-translational modifications (PTMs) of the causative proteins play an important role in the etiology of disease as they could either slow down or accelerate the disease progression. Alzheimer disease is associated with the aggregation and accumulation of two major protein aggregates-intracellular neurofibrillary tangles made up of microtubule-associated protein Tau and extracellular Amyloid-beta plaques. Post-translational modifications are important for the regulation of Tau`s function but an imbalance in PTMs may lead to abnormal Tau function and aggregation. Tau methylation is one of the important PTM of Tau in its physiological state. However, the methylation signature on Tau lysine changes once it acquires pathological aggregated form. Tau methylation can compete with other PTMs such as acetylation and ubiquitination. The state of PTM at these sites determines the fate of Tau protein in terms of its function and stability. The global methylation in neurons, microglia and astrocytes are involved in multiple cellular functions involving their role in epigenetic regulation of gene expression via DNA methylation. Here, we have discussed the effect of methylation on Tau function in a site-specific manner and their cross-talk with other lysine modifications. We have also elaborated the role of methylation in epigenetic aspects and neurodegenerative conditions associated with the imbalance in methylation metabolism affecting global methylation state of cells.
Keywords: Aggregation; Epigenetics; methylation; Methyltransferases; post-translational modifications; Tau

Microglial remodeling of actin network by Tau oligomers, via G protein-coupled purinergic receptor, P2Y12R-driven chemotaxis - Das, Rashmi; Chinnathambi, Subashchandrabose (Traffic, 2021)
Alzheimer's disease (AD) is associated with age-related neurodegeneration, synaptic deformation and chronic inflammation mediated by microglia and infiltrated macrophages in the brain. Tau oligomers can be released from damaged neurons via various mechanisms such as exosomes, neurotransmitter, membrane leakage etc. Microglia sense the extracellular Tau through several cell-surface receptors and mediate chemotaxis and phagocytosis. The purinergic receptor P2Y12R recently gained interest in neurodegeneration for neuro-glial communication and microglial chemotaxis towards the site of plaque deposition. To understand the effect of extracellular Tau oligomers in microglial migration, the P2Y12R-mediated actin remodeling, reorientation of tubulin network and rate of migration were studied in the presence of ATP. The extracellular Tau species directly interacted with P2Y12R and also induced this purinoceptor expression in microglia. Microglial P2Y12R colocalized with remodeled membrane-associated actin network as a component of migration in response to Tau oligomers. As an inducer of P2Y12R, ATP facilitated the localization of P2Y12R in lamellipodia and filopodia during accelerated microglial migration. The direct interaction of extracellular Tau oligomers with microglial P2Y12R would facilitate the signal transduction in both way, directional chemotaxis and receptor-mediated phagocytosis. These unprecedented findings emphasize that microglia can modulate the membrane-associated actin structure and incorporate P2Y12R to perceive the axis and rate of chemotaxis in Tauopathy.
Keywords: actin remodeling; Alzheimer' chemotaxis; microglia; migration; s disease; Tau Oligomers

Neem derivatives inhibits tau aggregation - Nalini, Gorantla Vijay; Das, Rashmi; Mulani, Fayaj Alam; Thulasiram, Hirekodathakallu V.; Chinnathambi, Subashchandrabose (Journal of Alzheimer s Disease Reports, 2021)
Tau is a phosphoprotein with natively unfolded conformation that functions to stabilize microtubules in axons. Alzheimer's disease pathology triggers several modifications in tau, which causes it to lose its affinity towards microtubule, thus, leading to microtubule disassembly and loss of axonal integrity. This elicit accumulation of tau as paired helical filaments is followed by stable neurofibrillary tangles formation. A large number of small molecules have been isolated from Azadirachta indica with varied medicinal applications. The intermediate and final limonoids, nimbin and salannin respectively, isolated from Azadirachta indica, were screened against tau aggregation. ThS and ANS fluorescence assay showed the role of intermediate and final limonoids in preventing heparin induced cross-β sheet formation and also decreased hydrophobicity, which are characteristic nature of tau aggregation. Transmission electron microscopy studies revealed that limonoids restricted the aggregation of tau to fibrils; in turn, limonoids led to the formation of short and fragile aggregates. Both the limonoids were non-toxic to HEK293T cells thus, substantiating limonoids as a potential lead in overcoming Alzheimer's disease.

Phosphoinositides signaling modulates microglial actin remodeling and phagocytosis in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Alzheimer's disease is one of the neurodegenerative diseases, characterized by the accumulation of abnormal protein deposits, which disrupts signal transduction in neurons and other glia cells. The pathological protein in neurodegenerative diseases, Tau and amyloid-P contribute to the disrupted microglial signaling pathways, actin cytoskeleton, and cellular receptor expression. The important secondary messenger lipids i.e., phosphatidylinositols are largely affected by protein deposits of amyloid-beta in Alzheimer's disease. Phosphatidylinositols are the product of different phosphatidylinositol kinases and the state of phosphorylation at D3, D4, and D5 positions of inositol ring. Phosphatidylinositol 3,4,5-triphosphate (PI 3, 4, 5-P3) involves in phagocytic cup formation, cell polarization, whereas Phosphatidylinositol 4,5-bisphosphate (PI 4, 5-P2)-mediates the process of phagosomes formation and further its fusion with early endosome.. The necessary activation of actin-binding proteins such as Rac, WAVE complex, and ARP2/3 complex for the actin polymerization in the process of phagocytosis, migration is regulated and maintained by PI 3, 4, 5-P3 and PI 4, 5-P2. The ratio and types of fatty acid intake can influence the intracellular secondary lipid messengers along with the cellular content of phaphatidylcholine and phosphatidylethanolamine. The Amyloid-beta deposits and extracellular Tau seeds disrupt phosphatidylinositides level and actin cytoskeletal network that hamper microglial-signaling pathways in AD. We hypothesize that being a lipid species intracellular levels of phosphatidylinositol would be regulated by dietary fatty acids. Further we are interested to understand phosphoinositide-based signaling cascades in phagocytosis and actin remodeling.
Keywords: actin remodeling; Alzheimer's disease; Dietary fatty acids; Phagocytosis; Phosphoinositides; PI3K signaling

Photodynamic sensitizers modulate cytoskeleton structural dynamics in neuronal cells - Dubey, Tushar; Chinnathambi, Subashchandrabose (Cytoskeleton, 2021)
The neuronal cytoskeleton plays a crucial role in maintaining cell integrity and functioning of neurons. Cytoskeleton deformities have been reported to be associated with neurodegenerative diseases thus; cytoskeleton can be targeted for therapeutic strategies. The therapeutic application of photosensitive molecule is termed as photodynamic therapy (PDT). PDT has been applied in the field of dermatology, cancer biology, and antimicrobial therapy. PDT induces several changes in cells, which include induction of apoptosis, DNA damage, and induction of inflammatory response. PDT has been also reported to modulate cytoskeleton such as actin dynamics. The in vitro studies suggested that PDT using dyes such as Toluidine Blue and Rose Bengal effectively modulated the actin cytoskeleton, neurite outgrowth, tubulin, and Tau aggregation. In this review, we focused on the effect of photosensitized molecules on various cytoskeleton proteins. We hypothesize that PDT could have potency against Alzheimer's disease and other neurodegenerative disorders.
Keywords: Actin; Alzheimer' cytoskeleton modulation; neuronal cytoskeleton; photodynamic therapy; s disease; Tubulin

Photodynamic treatment modulates various GTPase and cellular signalling pathways in Tauopathy - Dubey, Tushar; Chinnathambi, Subashchandrabose (Small GTPases, 2021)
ABSTRACTThe application of photo-excited dyes for treatment is known as photodynamic therapy (PDT). PDT is known to target GTPase proteins in cells, which are the key proteins of diverse signalling cascades which ultimately modulate cell proliferation and death. Cytoskeletal proteins play critical roles in maintaining cell integrity and cell division. Whereas, it was also observed that in neuronal cells PDT modulated actin and tubulin resulting in increased neurite growth and filopodia. Recent studies supported the role of PDT in dissolving the extracellular amyloid beta aggregates and intracellular Tau aggregates, which indicated the potential role of PDT in neurodegeneration. The advancement in the field of PDT led to its clinical approval in treatment of cancers, brain tumour, and dermatological acne. Although several question need to be answered for application of PDT in neuronal cells, but the primary studies gave a hint that it can emerge as potential therapy in neural cells.

G-protein coupled purinergic P2Y12 receptor interacts and internalizes TauRD-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer’s disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (TauRD) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, TauRD was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated TauRD internalization has demonstrated activation of microglia with an increase in the Iba1 level, and TauRD becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that TauRD is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated TauRD by lysosomal pathway. Altogether, microglial P2Y12R interacts with TauRD and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer’s disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau

G-protein coupled purinergic P2Y12 receptor interacts and internalizes Tau(RD)-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer's disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (Tau(RD)) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, Tau(RD) was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated Tau(RD) internalization has demonstrated activation of microglia with an increase in the Iba1 level, and Tau(RD) becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that Tau(RD) is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated Tau(RD) by lysosomal pathway. Altogether, microglial P2Y12R interacts with Tau(RD) and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer's disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau(RD)

Histone deacetylase-6 modulates Tau function in Alzheimer's disease - Qureshi, Tazeen; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-Molecular Cell Research, 2022)
Alzheimer's disease (AD), one of the major tauopathies, is multifactorial with a massive demand for disease modifying treatments rather than symptom management. An AD-affected neuron shows Tau depositions generated due to overload on the proteostasis machinery of the cell and/or abnormal post-translational modifications on Tau protein. Loss of memory or dementia is the most significant concern in AD, occurring due to the loss of neurons and the connections between them. In a healthy brain, neurons interact with the environment and each other through extensions and migratory structures. It can thus be safe to assume that Tau depositions affect these growth structures in neurons. A Histone Deacetylase, HDAC6, has shown elevated levels in AD while also demonstrating direct interaction with the Tau protein. HDAC6 interacts with multiple proteins in the cell and is possibly involved in various signalling pathways. Its deacetylase activity has been a point of controversy in AD; however other functional domains remain unexplored. This review highlights the beneficial potential of HDAC6 in AD in mediating both Tau proteostasis and cytoskeletal rewiring for the neuritic extensions through its Ubiquitin Binding domain (HDAC6 ZnF UBP).
Keywords: Actin; Cytoskeleton; HDAC6; Microtubules; Proteostasis; Tau; ZnF UBP domain

Role of cysteines in accelerating Tau filament formation - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Journal of Biomolecular Structure & Dynamics, 2022)
Alzheimer's disease is majorly associated with intracellular accumulation of Tau into paired helical filaments and tangles. The self-aggregated dimeric and oligomeric species of Tau formed are more toxic to neuronal cells and acts as seeds for filament formation. The two cysteine residues and the two hexapeptide regions of full-length Tau play a key role in initialization and filament formation during Tau aggregation. The role of cysteine residues in Tau aggregation has been studied by in-vitro aggregation assay that was measured by Thioflavin S fluorescence to observe the kinetics of aggregation. In this study, we have performed in-vitro aggregation assay with recombinant full-length Tau and the cysteine mutants to understand the mechanism of cysteine independent Tau aggregation. Here, we report that cysteine mutant full-length Tau can aggregate to form filaments under in-vitro conditions. To visualize the polymorphisms of Tau and cysteine mutants under different aggregation conditions anionic cofactor, heparin was employed. Wild-type Tau showed rapid aggregation to form oligomers and filaments. On the other hand, the cysteine mutant delayed the initial Tau aggregation. This indicates the importance of cysteine residues in accelerating initial Tau nucleation for its aggregation. The filament morphology of wild-type and cysteine mutant Tau has been characterized using transmission electron microscopy and high-resolution transmission electron microscopy. Communicated by Ramaswamy H. Sarma
Keywords: Heparin-induced aggregation; Paired helical filaments; Tau Aggregation; Tau Oligomers; tau protein

Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation

Microglia degrade Tau oligomers deposit via purinergic P2Y12-associated podosome and filopodia formation and induce chemotaxis - Chinnathambi, Subashchandrabose; Das, Rashmi (Cell and Bioscience, 2023)
BackgroundTau protein forms neurofibrillary tangles and becomes deposited in the brain during Alzheimer's disease (AD). Tau oligomers are the most reactive species, mediating neurotoxic and inflammatory activity. Microglia are the immune cells in the central nervous system, sense the extracellular Tau via various cell surface receptors. Purinergic P2Y12 receptor can directly interact with Tau oligomers and mediates microglial chemotaxis via actin remodeling. The disease-associated microglia are associated with impaired migration and express a reduced level of P2Y12, but elevate the level of reactive oxygen species and pro-inflammatory cytokines.ResultsHere, we studied the formation and organization of various actin microstructures such as-podosome, filopodia and uropod in colocalization with actin nucleator protein Arp2 and scaffold protein TKS5 in Tau-induced microglia by fluorescence microscopy. Further, the relevance of P2Y12 signaling either by activation or blockage was studied in terms of actin structure formations and Tau deposits degradation by N9 microglia. Extracellular Tau oligomers facilitate the microglial migration via Arp2-associated podosome and filopodia formation through the involvement of P2Y12 signaling. Similarly, Tau oligomers induce the TKS5-associated podosome clustering in microglial lamella in a time-dependent manner. Moreover, the P2Y12 was evidenced to localize with F-actin-rich podosome and filopodia during Tau-deposit degradation. The blockage of P2Y12 signaling resulted in decreased microglial migration and Tau-deposit degradation.ConclusionsThe P2Y12 signaling mediate the formation of migratory actin structures like- podosome and filopodia to exhibit chemotaxis and degrade Tau deposit. These beneficial roles of P2Y12 in microglial chemotaxis, actin network remodeling and Tau clearance can be intervened as a therapeutic target in AD.
Keywords: Filopodia; microglia; migration; Podosome; Tau Oligomers

Tau aggregates improve the Purinergic receptor P2Y12-associated podosome rearrangements in microglial cells - Chinnathambi, Subashchandrabose; Das, Rashmi; Desale, Smita Eknath (Biochimica Et Biophysica Acta-Molecular Cell Research, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is associated with protein misfolding, plaque accumulation, neuronal dysfunction, synaptic loss, and cognitive decline. The pathological cascade of AD includes the intracellular Tau hyperphosphorylation and its subsequent aggregation, extracellular Amyloid-& beta; plaque formation and microglia-mediated neuroinflammation. The extracellular release of aggregated Tau is sensed by surveilling microglia through the involvement of various cell surface receptors. Among all, purinergic P2Y12R signaling is involved in microglial chemotaxis towards the damaged neurons. Microglial migration is highly linked with membrane-associated actin remodeling leading to the phagocytosis of extracellular Tau species. Here, we studied the formation of various actin structures such as podosome, lamellipodia and filopodia, in response to extracellular Tau monomers and aggregates. Microglial podosomes are colocalized with actin nucleator protein WASP, Arp2 and TKS5 adaptor protein during Tau-mediated migration. Moreover, the P2Y12 receptors were associated with F-actin-rich podosome structures, which signify the potential of Tau aggregates in microglial chemotaxis through the involvement of actin remodeling.
Keywords: Alzheimer `s disease; Filopodia; microglia; Podosome; Tau aggregates

TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization: a specialized Tau perspective - Kapoor, Mahima; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2023)
Microtubule-associated protein, Tau has been implicated in Alzheimer's disease for its detachment from microtubules and formation of insoluble intracellular aggregates within the neurons. Recent findings have suggested the expulsion of Tau seeds in the extracellular domain and their prion-like propagation between neurons. Transforming Growth Factor-beta 1 (TGF-beta 1) is a ubiquitously occurring cytokine reported to carry out immunomodulation and neuroprotection in the brain. TGF-beta-mediated regulation occurs at the level of neuronal survival and differentiation, glial activation (astrocyte and microglia), amyloid production-distribution-clearance and neurofibrillary tangle formation, all of which contributes to Alzheimer's pathophysiology. Its role in the reorganization of cytoskeletal architecture and remodelling of extracellular matrix to facilitate cellular migration has been well-documented. Microglia are the resident immune sentinels of the brain responsible for surveying the local microenvironment, migrating towards the beacon of pertinent damage and phagocytosing the cellular debris or patho-protein deposits at the site of insult. Channelizing microglia to target extracellular Tau could be a good strategy to combat the prion-like transmission and seeding problem in Alzheimer's disease. The current review focuses on reaffirming the role of TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization and considers utilizing the approach of TGF-beta-triggered microglia-mediated targeting of extracellular patho-protein, Tau, as a possible potential strategy to combat Alzheimer's disease.
Keywords: Alzheimer's disease; Cytoskeleton reorganization; Extracellular Tau; microglia; TGF-beta; TGF-beta 1

Dual modification of tau by pseudophosphorylation and glycation does not enhance amorphous aggregation - Chinnathambi, Subashchandrabose; Sonawane, Shweta Kishor; Chandrashekar, Madhura; Chidambaram, Hariharakrishnan; Thulasiram, Shrivatsa; Kulkarni, Mahesh J. (Cellular Physiology and Biochemistry, 2024)
<h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Background/Aims: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The neurofibrillary tangles consisting of Tau protein are an important pathology in Alzheimer’s disease. The paired helical filaments of Tau form most of the NFTs. These PHFs of Tau are found to carry numerous post-translational modifications, which stabilize them and aid in aggregation. The mechanistic function of Tau is to bind and stabilize the axonal microtubules. Hyperphosphorylation of Tau causes it to compromise its physiological function and accumulate in the neurons in the form of aggregates. Such residue-specific phosphorylation has been studied by employing Tau pseudophosphorylation mutants. But in addition to phosphorylation, several other modifications also aid in stabilizing the Tau PHF. Glycation is one such non-enzymatic PTM caused by sugars and their reactive intermediates. In this study, we employed the pseudophosphorylated Tau double mutants (262/404D, 262/396D, and 231/262) for studying their modification by methyl glyoxal, a reactive intermediate of glucose metabolism.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Methods: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> We studied various biophysical properties like aggregation propensity, Advanced glycation end-product formation, and global conformation of the Tau with dual modifications. Our study includes the use of <i style="box-sizing: border-box; color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">in vitro <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">techniques e.g., ThS fluorescence assay, electron microscopy, CD spectroscopy, SDS-PAGE.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Results: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The overall result of the study suggest that the MG-induced Tau aggregation is influenced by the residue-specific Tau phosphorylation.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Conclusion: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> In conclusion, the combinatorial effect of discreet PTMs on Tau function could lead to a better understanding of Tauopathy.

Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation